Assessment of the Safety and Efficiency of a Preperitoneal Continuous Infusion Using Bupivacaine after Abdominal Laparotomy in Digestive Carcinology - Hayat Ben-Saghroune; Mohammed Abdessadek; Sanae Achour; Youssef Kfal; Abderrahim El Bouazzaoui; Nabil Kanjaa; Hicham Sbai (Anesthesiology Research and Practice)
The purpose of this paper is to evaluate the safety and efficacy of continuous preperitoneal wound infiltration using bupivacaine after abdominal laparotomy in relation to plasma bupivacaine concentration and visual analog scale. Our study was performed on 60 adult patients with digestive cancer, operated at laparotomy, and randomized into two groups: bupivacaine and saline groups. The wound infiltration was through a multiperforated catheter along the scar. For the bupivacaine group, 0.25% bupivacaine was used; however, for the saline group, only saline (0.9%) was infiltrated. The pain was assessed by using the visual analog scale (VAS) in both groups. Plasma bupivacaine concentration was measured by high-performance liquid chromatography. The bupivacaine group had significantly lower postoperative morphine consumption and lower postoperative pain than the saline group (P < 0.0001). The majority of patients in the bupivacaine group had significant relief with the VAS scores of less than 3/10 cm at rest and 6/10 cm on mobilization. However, for the saline group, the VAS scores were higher than 6/10 cm either at rest or with mobilization. There was no clinical sign of toxicity and no technical complications for the bupivacaine group. Only eleven patients required morphine in this group, but the majority of patients received morphine at different doses in the saline group. Plasma bupivacaine was at very low concentrations. Overall, the current study has confirmed that continuous preperitoneal wound infiltration as postoperative analgesia is a simple, effective, and safe technique. It allows decreasing of morphine consumption and subsequently canceling their side effects.